Smile aesthetics and malocclusion in advertising models on Nigerian billboards - O. D. Otuyemi (Nigerian Dental Association, 2008)
Objective: There is a growing influence of advertising media on the perception of dental appearance in the Nigerian society. This study examined the portrayal of malocclusion on advertising billboards that is directed at the Nigerian public Method: A representative selection of 100 advertising models on billboards from three major Nigerian cities was investigated. The prevalence and severity of malocclusions observed including the median diastema, which is of cultural importance, were assessed using a modification of Aesthetic Component of Index of Orthodontic Treatment Need (IOTN). Intra-examiner calibration of all the smiles showed adequate agreement. Result: It showed that the aesthetic scores were low for the majority of models (94%) indicating "no need or a borderline need" for treatment, whilst insignificant models (6%) exhibited a "definite need for treatment". However, median diastema, a sign of personal beauty in this cultural setting did not feature prominently in the smile aesthetics. Conclusion: The study concluded that the portrayal of occlusal disharmonies on models in billboards may not be generalized to the entire Nigerian population.